Case File: Point-of-care ultrasound should end the outdated practice of "marking for a tap" - Anna Platovsky; Benjamin T. Galen (CINQUILL Medical Publishers Inc., 2017)
A 55 year old man with a history of alcoholic cirrhosis decompensated by esophageal varices status post banding presented to the emergency room with abdominal pain.  He also noted increased abdominal girth with associated poor oral intake and early satiety as well as a 10 lb. weight gain over 2 weeks.  On examination, the patient was afebrile with stable vital signs and no respiratory distress.  His abdominal examination revealed tense ascites with mild tenderness to palpation of the left upper quadrant.  There was no jaundice or asterixis. Laboratory testing was significant for mild thrombocytopenia but no leukocytosis or abnormal liver tests. Liver synthetic function was preserved.